Evaluation of histological post‐mortem changes in farmed Atlantic salmon (Salmo salar L.) at different time intervals and storage temperatures. Issue 10 (29th June 2022) - Furnesvik, Lisa; Erkinharju, Toni; Hansen, Miroslava; Yousaf, Muhammad Naveed; Seternes, Tore
Abstract: The aim of this study was to evaluate histologic post‐mortem autolytic changes in farmed Atlantic salmon. The fish were either stored at room temperature (RT, 21°C), refrigerated (4°C) or frozen (−20°C), while fish necropsy was performed at 0, 1, 4, 24 and 48 h post‐storage (hps). In addition, gills were sampled at 0, 5, 10, 15, 30 and 45 min post‐storage (mps) at room temperature (RT). The haematoxylin and eosin‐stained tissue slides were evaluated and scored by using a semi‐quantitative scoring system. Our findings demonstrated gills and pyloric caeca/pancreas as the most severely autolysed organs while heart and skeletal musculature were least affected. Generally, moderate to severe autolysis appeared first at 4 hps, while severe changes were seen at 24 hps. Gills demonstrated autolytic changes as early as 10 mps and pyloric caeca/pancreas at 1 hps. Freezing did not prevent the autolysis and even contributed to freezing artefacts, which may lead to misdiagnosis. Keeping organs refrigerated slowed the autolytic progress within the first 4 hps marginally. This study recommends gills and pyloric caeca/pancreas should be sampled as early as possible, at least within 10 min post‐necropsy.